2006
DOI: 10.1159/000092376
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline and Dexamethasone Induce Peroxisome Proliferator-Activated Receptor-γ Expression in Human Eosinophils

Abstract: Eosinophils are major effector cells in allergic diseases including asthma. Peroxisome proliferator-activated receptor-γ (PPARγ) is a nuclear receptor that regulates immune reaction. We have previously demonstrated that human eosinophils express PPARγ and that stimulation with a synthetic agonist for PPARγ attenuated the factor-induced eosinophil survival and chemotaxis. However, the modulator of the eosinophil PPARγ expression has not yet been studied. In this study, we investigated the effect of theophylline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…We first studied the effect of 17β-estradiol on PPARγ protein levels using a flow cytometer. In line with our previous report, purified fresh eosinophils constitutively expressed PPARγ [5, 16, 17]. Eosinophils were cultured with various concentrations of 17β-estradiol for 24 h, followed by measurement of PPARγ expression (fig.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…We first studied the effect of 17β-estradiol on PPARγ protein levels using a flow cytometer. In line with our previous report, purified fresh eosinophils constitutively expressed PPARγ [5, 16, 17]. Eosinophils were cultured with various concentrations of 17β-estradiol for 24 h, followed by measurement of PPARγ expression (fig.…”
Section: Resultssupporting
confidence: 56%
“…Although the influence of estradiol on cell function was previously assigned exclusively to genomic reaction, it is known that estradiol activates the membrane form of ER and can rapidly induce intracellular cyclic AMP (cAMP) elevation [24]. Recently, we found that the bronchodilators theophylline and procaterol upregulated PPARγ mRNA and protein expression in eosinophils [15, 16]. Because the functions of these drugs are mediated through cAMP signaling, elevated cAMP in eosinophils might play a role in augmentation of PPARγ expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it has been postulated that the anti-inflammatory effects may be due to mechanisms other than phosphodiesterase inhibition. Adenosine receptor antagonism (27), an increase in histone deacetylase activity (28), and/or enhanced messenger RNA and protein levels of peroxisomal proliferator-activated receptor-gamma (PPAR-gamma) expression (29) have all been reported as potential explanations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the PPARγ expression in eosinophils was unaltered on stimulation with IL-5, which is a major eosinophil-activating cytokine that is produced abundantly at allergic inflammatory sites [26]; further, it showed no correlation with the activation marker CD25 or eosinophilic cationic proteins in serum [32]. Recent studies in our laboratory indicated that de novo synthesis of PPARγ was induced in human eosinophils by culturing them along with drugs such as β-adrenoceptor agonist or theophylline at therapeutic concentrations [26, 33]. Therefore, an alternative explanation is that these drugs might augment PPARγ expression in asthmatic subjects.…”
Section: Eosinophils Express Pparγ: An Intracellular Target Of 15d-pgj2mentioning
confidence: 99%